SI-MOHONBANGET: Sistem Informasi Permohonan Pembangunan & Pengembangan Aplikasi Berbasis Website di Lingkungan Kabupaten Musi Banyuasin - Muhammad Adji Arrafi; Rahayu Amalia; Nyimas Sopiah; Fitri Purwaningtias (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Public services are one of the obligations that local governments must fulfill to meet the rights of their citizens. In its implementation, local governments leverage technological advancements to save costs and conserve resources, one of which is by creating an online Application for Development and Application Development Information System (SI-MOHONBANGET). This integrated national digital service can enhance the quality of government administrative services and public services that are more systematic, straightforward, and integrated. Currently, the development of information and communication technology in regional apparatus at the Communication and Information Office, particularly in the field of Applications and Informatics, is still conducted manually, requiring individuals to visit the office directly. This process is time-consuming and prone to errors, as well as data corruption, while also minimizing the occurrence of data redundancy. Therefore, it is essential to develop an application for regional apparatus to facilitate online applications for the construction and development of applications with substantial storage capacity, allowing for periodic data checks. The method used in this research is web engineering. The result of this study is the availability of an application that can be utilized to submit requests for the development and establishment of web-based applications within the Government of Musi Banyuasin Regency.